E-Commerce Transformation in Indonesia: Intellectual Property Rights Protection in the Local Digital Market - Ary Widiani, Ni Luh Gede Nita; Laksmi Dewi, Cokorde Istri Dian (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The transformation  of e-commerce in Indonesia has become a significant phenomenon in today's digital era. This article explores the impact of the transformation on the protection of Intellectual Property Rights (IPR) in the local digital market. Through an analysis of IPR-related policies and practices, this article attempts to understand how these efforts affect copyright, trademark, and patent protection amid the rapid development of e-commerce. In addition, this article also highlights the challenges and opportunities faced in harmonizing IPR principles with the dynamics of Indonesia's ever-evolving digital market. This article aims to provide a better understanding of how changes in the digital business environment are affecting protection efforts against copyrights, trademarks, and patents. The results of this article reveal shifting business patterns and new challenges in the protection of Intellectual Property Rights (IPR) in Indonesia's digital market, while also highlighting the importance of developing inclusive and balanced regulations to optimize IPR protection and support inclusive economic growth and promote social justice